Strapdown inertial navigation technology - Titterton, D. H. (David H.); Weston, J. L. (John L.). (London, United Kingdom Institution of Engineering and Technology, 2004)
Inertial navigation is widely used for the guidance of aircraft, missile, ships, and land vehicles, as well as in a number of novel applications such as surveying underground pipelines in the drilling operations. This book sets out to provide a clear and concise description of the physical principles of inertial navigation, the associated growth of errors and their compensation. there is also a detailed treatment of recent developments in inertial sensor technology and a description of techniques for implementing and evaluating such systems.This new edition includes a number of refinements covering sensor technology, geodesy and error modelling, plus new chapters on MEMS technology and inertial systems applications.
Co-published by the American Institute of Aeronautics and Astronautics.
Previous ed.: London: Peter Peregrinus, 1997.
Electronic reproduction.
Keywords: Inertial navigation (Aeronautics); Inertial navigation systems; Electronic books